Efficacy of Mosapride Citrate in Combination with Oral Mechanical Bowel Preparation for Colonoscopy - Jaruvongvanich, Pornchanok; Sirikurnpiboon, Siripong (The Thai Journal of Surgery, 2022)
Objective: The present study aimed to evaluate the efficacy, in terms of bowel preparation quality, and safety of adjunctive mosapride citrate with oral mechanical bowel preparation for colonoscopy. Methods: We conducted a randomized, controlled trial, mosapride in addition to mechanical bowel preparation. Of 330 patients undergoing colonoscopy, 158 were randomized to an additional 10 mg of mosapride citrate (intervention group) to oral mechanical bowel preparation, and 172 received only oral mechanical bowel preparation (control group). Patients completed questionnaires reporting the acceptability and tolerability of the bowel preparation process. The efficacy of bowel preparation was assessed by colonoscopists using a Boston Bowel Preparation Scale (BBPS). Results: A total of 330 patients were included in the analysis. In the intervention group, optimal excellent bowel preparation rates were significantly higher compared with the control group (81.6% vs. 64.5%, p < 0.001). The incidence of adverse events was similar in both groups. Moreover, patients significantly favored intervention group over control, reflected by less clinical symptoms of nausea, abdominal pain, abdominal distension and willingness to repeat the same regimen Conclusion: Mosapride citrate may be an effective and safe adjunct to oral mechanical bowel preparation for colonoscopy that leads to improve quality of bowel preparation and patient compliance.